The origin of surface microstructure evolution in sliding friction. (August 2018) - Greiner, Christian; Liu, Zhilong; Schneider, Reinhard; Pastewka, Lars; Gumbsch, Peter
Abstract: A typical tribologically induced microstructure displays a discontinuity parallel to the surface separating the near-surface layer from the bulk. Despite its ubiquitous observation, the origin of this layer underneath the surface remains elusive. Here, we show that already after the first loading pass a localized dislocation structure is found at a depth of 100–150 nm. This structure is linked to the inhomogeneous stress field under the moving indenter, where dislocations are trapped when the stress drops below the material's yield stress. Control of the initial tribological loading could therefore be exploited to design surfaces and materials with superior tribological properties. Graphical abstract: Unlabelled Image